QUALITATIVE ANALYSIS OF FACTORS AFFECTING SECURITY AND ORDER IN CLASS IIB CORRECTIVE INSTITUTIONS IN SIBORONGBORONG - Feriandi, Iin; Simanjuntak, Meitisa Vanya (Universitas Nusa Cendana, 2025)
In an effort to improve security and order in Siborongborong Class IIB Correctional Institution, several strategic steps need to be taken. First, it is necessary to improve and develop more adequate facilities and infrastructure, including investment in security technology such as CCTV, X-Ray scanners, and other security equipment. Second, increasing the number of officers needs to be prioritized, accompanied by training and skills development to improve service quality. Third, diversification of guidance and rehabilitation programs that can have a positive impact on WBP, through the provision of various education and skills programs and regular evaluation to ensure their effectiveness. Furthermore, the strengthening of a consistent supervision system and the implementation of good SOPs are very important, especially in checking luggage, visits, and handling complaints from WBP. Finally, effective communication between officers and prisoners, as well as a persuasive approach, needs to be promoted in daily interactions to create positive relationships and a conducive atmosphere, while minimizing the potential for security disturbances. With these measures, it is expected that a safer environment will be created and support the rehabilitation process in prisons. Keywords: Security and Order; Citizens Fostering; Institution Community